THE SPATIAL CONFIGURATION OF TRADITIONAL URBAN CORE OF ZAKHO CITY - RASWOL , LAYLA M.; KHORSEED, JOWAN BAYEZ (Journal of Duhok University, 2023)
The conventional urban core is commonly described as an organic entity. The urban environment holds inherent adaptability and responsiveness to the dynamic influences of social, cultural, and economic factors, which impact its various components and elements of urban design. This phenomenon leads to alterations in the spatial arrangement of the urban environment, resulting in the creation of distinct spatial structures that correspond to specific time periods. The objective of this study is to gain insight into the spatial configuration of the built environment in traditional urban cores, with a focus on understanding how these configurations relate to culture-specific human preferences regarding spatial organization. The research question aims to determine the spatial syntactic characteristics of the traditionally developed built environment. The urban core will be delineated by a set of configuration parameters that establish its spatial organization, typology, and organic structure based on user preferences. The study will utilize the Space Syntax methodology and urban centrality indexes (UNA) in ArcGIS by utilizing the existing urban core plans in order to accomplish the research objectives. The outcomes of the analysis will ascertain the various spatial arrangements and subsequently extrapolate the rationales and influential factors behind these arrangements.